Review of Happiness in Nineteenth-Century Ireland, by Mary Hatfield (ed.) - Madalina Armie (Review of Irish Studies in Europe, 2022)
Review of Happiness in Nineteenth-Century Ireland, by Mary Hatfield (ed.) (Liverpool University Press, 2021). ISBN 978-1-800-34825-7, 248pp, £90.00 (hardback)